HERMENEUTICS OF LINGVOPOETIC PARADIGMS IN NAVAI (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
Our generation should be more knowledgeable, healthier and of course happier than us”. These words of the president of Uzbekistan Shavkat Mirziyayev nowadays became the motto of our republic. Today in our country there are a lot of opportunities for young generation to accomplish the aim which was stated by our president. Using these opportunities and support by our country young generation is also trying to discover the unlimited world of different subjects and sciences. Among these subjects the Art occupies a great position too. Especially, the literature has always been the first and foremost subject which impressed our nation all the time.The article analyzes the principles of social and political factors in the creation of art poetic language and hermeneutic analisis of the text in uzbek classic lyrics. Unique masterpieces of Uzbek Literature have been translated into a number of foreign languages for centuries. For instance, the works of Ahmad Yassaviy (11-century),  Yusuf Hos Hojib’s “Kutadgu Bilig”(12-century), “Muhabbatnoma”  written by  Khorazmiy  (14-century), literary works of Lutfiy, Navoiy (15-century), Babur (16-century), Mashrab, Turdi, “Temur Tuzuklari” revealing Tamerlane’s life and his conquests and many others are translated into English, Russian, French, German and many other languages. Numerous scientific researches devoted to these works intrigue any audience, indeed. It should be emphasized with delight that a number of ancient Turkish-Uzbek literary essays were founded, reviewed and printed with initiatives of some European researches.Uzbeks are very curious people and always like to learn something new. That’s why from Ancient times our ancestors had strong relationships with not only countries of Asia but also the countries of the world. And indeed, they exchanged their cultures and national riches with each other. In these exchanges the literature has no considerable place.